Relevansi Hadis al-Ifki dalam Melindungi Martabat Perempuan di Era Digital: Telaah atas Kekerasan Verbal dan Siber - Siregar, Uzair Nazri (Yayasan Albahriah Jamiah Indonesia, 2025)
This study aims to analyze the relevance of the hadith al-Ifki in protecting women’s dignity in the digital era, especially in the context of verbal and cyber violence. The hadith al-Ifki, which tells of slander against Aisha, the wife of the Prophet Muhammad, is an important basis in understanding the protection of women’s honor and dignity. This study uses a qualitative method with a descriptive-analytical approach. The analysis was carried out by connecting the principles of protecting women’s dignity in the hadith al-Ifki with the practice of digital violence that occurs today. The results of the study show that the hadith al-Ifki teaches the importance of maintaining women's honor and integrity, and advises Muslims to fight slander with a wise and respectful approach. In the context of verbal and cyber violence, this hadith is relevant as a moral and ethical basis for protecting women's dignity in cyberspace. In conclusion, the hadith al-Ifki provides important guidelines in dealing with issues of verbal and cyber violence against women, as well as being a basis for protecting women’s dignity in the increasingly developing digital era.